Modeling the effects of water regulation on the population viability of a threatened amphibian - Rupert Mathwin; Skye Wassens; Matthew S. Gibbs; Jeanne Young; Qifeng Ye; Frédérik Saltré; Corey J. A. Bradshaw (Ecosphere, 2023)
Abstract The regulation of river systems alters hydrodynamics and often reduces lateral connectivity between river channels and floodplains. For taxa such as frogs that rely on floodplain wetlands to complete their life cycle, decreasing inundation frequency can reduce recruitment and increase the probability of local extinction. We virtually reconstructed the inundation patterns of wetlands under natural and regulated flow conditions and built stochastic population models to quantify the probability of local extinction under different inundation scenarios. Specifically, we explored the interplay of habitat size, inundation frequency, and successive dry years on the local extinction probability of the threatened southern bell frog Litoria raniformis in the Murray River floodplains of South Australia. We hypothesized that the changes to wetland inundation resulting from river regulation are driving L. raniformis declines in this semiarid system. Regulation has reduced the inundation frequency of essential habitats below critical thresholds for the persistence of many fresh water‐dependent species. Successive dry years raise the probability of local extinction, and these effects are strongest in smaller wetlands. Larger wetlands and those with more frequent average inundation are less susceptible to these effects. Elucidating these trends informs the prioritization of intervention sites and the frequency of conservation interventions. Environmental water provision (through pumping or the operation of flow‐regulating structures) is a promising tool to reduce the probability of breeding failure and local extinction. Our modeling approach can be used to prioritize the delivery of environmental water to L. raniformis and potentially many other frog species.